Metabolic Responses to Epinephrine by Periparturient Dairy Cows Fed Prepartum Diets Differing in Predicted Metabolizable Protein Supply - Underwood, John P.; Drackley, James K. (Frontiers in Animal Science, 2022)
Twelve nonlactating cows in second or greater pregnancies were assigned to a low MP diet (LMP) formulated to provide approximately 900 g/d MP or a high MP diet (HMP) to provide approximately 1100 g/d MP. Cows received prepartum diets from 28 d before expected parturition to day of parturition, and then received a common lactation diet until 35 d postpartum. Blood was sampled weekly to d -7, daily to d 7, and weekly through d 35 relative to parturition for analysis of glucose, nonesterified fatty acids (NEFA), 3-hydroxybutyrate (BHB), urea N, and total protein concentrations. Epinephrine challenges were conducted on d -10 before expected parturition, and d 7 and d 14 postpartum. Epinephrine (1.4 g/kg BW) was administered via jugular vein and blood was collected from the opposite jugular vein from –45 min to +120 min relative to epinephrine administration. Plasma was analyzed for glucose and NEFA concentrations. Prepartum dry matter intake (DMI; 14.7 and 12.6 ± 1.5 kg/d for LMP and HMP, respectively), postpartum DMI (21.4 and 19.4 ± 1.3 kg/d for LMP and HMP), and 4% fat-corrected milk (FCM; 37.0 and 36.8 ± 1.5 kg/d for LMP and HMP) did not differ significantly between diets. Cows fed HMP had higher plasma concentrations of urea N prepartum than cows fed LMP (14.0 vs 7.9 ± 0.8 mg/dL). Cows fed HMP tended to have greater prepartum concentrations of total protein in plasma than those fed LMP (7.5 vs 7.0 ± 0.2 g/dL). Area under the curve (AUC) for NEFA response to epinephrine did not differ between diets but differed by day relative to parturition (8,284; 29,018; and 18,219 ±2302 min × (eq/(L)) for d –10, d 7, and d 14, respectively). Maximal response of NEFA concentration to epinephrine was greater for HMP than for LMP (744 vs. 438 ± 72 µeq/L). Glucose AUC did not differ between diets or among days. Lipolytic response, but not glucose response, to epinephrine was enhanced during the early postpartum period relative to the late dry period. However, those responses were not affected by prepartum MP supply.